2011
DOI: 10.1017/s0022215111002283
|View full text |Cite
|
Sign up to set email alerts
|

Pneumosinus dilatans, pneumocoele or air cyst? A case report and literature review

Abstract: Whilst the nomenclature of this pathology is confusing, distinctions of terminology do not alter the management. Hence, we support the use of the term 'air cyst', to incorporate all these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…По мнению B.M. Teh et al [11], проанализи ровавших большой объем публикаций, избыточ ная аэрация ВЧП чаще всего приводит к ее рас ширению кзади и медиально в подвисочную ямку и выше в область нижней стенки глазницы. Чаще поражается правая гайморова пазуха.…”
Section: Discussionunclassified
“…По мнению B.M. Teh et al [11], проанализи ровавших большой объем публикаций, избыточ ная аэрация ВЧП чаще всего приводит к ее рас ширению кзади и медиально в подвисочную ямку и выше в область нижней стенки глазницы. Чаще поражается правая гайморова пазуха.…”
Section: Discussionunclassified
“…The treatment plan should be tailored according to the patient's severity of symptoms, the status of the cortical bone, the size of the sinus, and the co-existence of other nasal conditions such as DNS or HIT. Moreover, one of the most common procedures performed is the creation of a naso-antral window, mainly to equilibrate the intrasinus pressure [8] . Another surgical approach for managing maxillary sinus air cyst is needle puncture.…”
Section: Discussionmentioning
confidence: 99%
“…Teh et al ,7 in a literature review, mentioned that the mean age of presentation was 27 years (range, 9–62 years), with a slight male predilection. The authors identified a total of 36 reported cases involving the maxillary sinus of which 2 cases also involve the mastoid air cells 8 9.…”
Section: Discussionmentioning
confidence: 99%